ISSUES OF DIGITALIZATION OF ENTREPRENEURSHIP BASED ON INNOVATIVE TECHNOLOGIES - Bektemirov Abduxamid Abdumalikovich; Ortiqboev Elbek Diyorjon oʻg‘li (Western European Studies, 2024)
This article delves into the challenges and opportunities presented by the digitalization of entrepreneurship based on innovative technologies. As the business landscape continues to evolve rapidly, entrepreneurs are faced with the task of harnessing cutting-edge technologies to drive innovation, enhance competitiveness, and navigate market dynamics. Through an analysis of current trends and case studies, this article explores key issues such as technology adoption, disruption of traditional business models, implications for competitiveness and innovation, and strategies for effective navigation. By providing insights into the intersection of entrepreneurship and innovative technologies, this article aims to equip entrepreneurs with the knowledge and tools necessary to thrive in an increasingly digitalized economy
Keywords: digitalization; entrepreneurship; innovative technologies; strategic navigation